Peningkatan Kemampuan Komunikasi Verbal Melalui Penggunaan Website H5P pada Murid Autis Kelas I di SLB Katolik Rajawali Makassar - Priska Justicia; Usman Bafadal; Bastiana Bastiana (STIKes Ibnu Sina Ajibarang, 2024)
The problem in writing this thesis was a class I autistic student at the Rajawali Catholic SLB Makassar who experienced difficulties in verbal communication. The aims of this research were to determine: (1) The verbal communication abilities of class I autistic students at Rajawali Catholic SLB Makassar before using the H5P website, (2) The verbal communication abilities of class I autistic students at Rajawali Catholic SLB Makassar after using the H5P website, (3) Improving verbal communication skills in class I autistic students at the Rajawali Catholic SLB Makassar using the H5P website. This research uses a quantitative approach and descriptive research type. The data collection technique in this research is an oral test. The data obtained was processed descriptively quantitatively to determine the increase in verbal communication before and after using the H5P website in class I autistic students at Rajawali Catholic SLB Makassar using pretest and posttest scores. The results of the research showed that the verbal communication skills of class I autistic students at the Rajawali Catholic SLB Makassar before using the H5P website were in the poor category, then after using the H5P website there was an increase to the sufficient category. Conclusion The results of this research are that there is an increase in verbal communication skills through the use of the H5P website in class I autistic students at the Rajwali Catholic SLB Makassar.